Trace-metal contamination in proton exchange membrane fuel cells caused by laser-cutting stains on carbon-coated metallic bipolar plates. (14th April 2021) - Novalin, Timon; Eriksson, Björn; Proch, Sebastian; Bexell, Ulf; Moffatt, Claire; Westlinder, Jörgen; Lagergren, Carina; Lindbergh, Göran; Lindström, Rakel Wreland
Abstract: Trace-metal contamination poses a threat to performance and stability of proton exchange membrane fuel cells (PEMFCs). In this study the source of origin and degree of metal dissolution from carbon-coated 316L bipolar plates (BPPs) are evaluated after a long-term PEMFC test run under conditions resembling a real-life automotive application. Despite intact carbon-coating, metal dissolution occurs from uncoated oxycarbide stains on the plates' surface. Which correlates with post-mortem detection of chromium, iron and nickel in the membrane electrode assembly. The rate of cell voltage decrease throughout the high current operations is found to be twice as high in the presence of metal ions. Metal dissolution can be correlated with transients in cell voltage during dynamic current load cycling as a result of temporary global fuel starvation. The observed difference in metal dissolution on the anode and cathode BPP indicates weak galvanic coupling between the bipolar plate(s) and the electrode layer(s). Highlights: Simultaneous in situ measurement of cell voltage and interfacial contact resistance. Source of metal contamination were uncoated metal oxycarbide stains on bipolar plates. Metal dissolution was correlated with voltage transients caused by fuel starvation. Asymmetric dissolution indicates galvanic decoupling between plates and electrodes.